Developing dynamics in South Asia: a reflection on recent political change in Sri Lanka - Mohamed Zacky, Mohamed Fouz (Centre for Islamisation (CENTRIS), IIUM, 2024)
In just three months, South Asia has seen two significant political changes that could have far-reaching local, regional, and even global political consequences: the fall of Sheikh Hasina and the rise of new student power, and the victory of Anura Kumara Dissanayake (AKD) in the Sri Lankan presidential elections. These events have become important milestones in South Asian politics, leading political analysts to debate their similarities and differences. The important similarity of both events is that both new power dynamics have been shaped by revolutions. That being said, this article mainly aims to delve into the rise of AKD after the presidential elections and the factors that facilitated this change, to understand the evolving dynamics of Sri Lankan politics and its implications on Muslim minorities in the country.